Evaluasi Implementasi Permintaan Rekam Medis Operasi Elektif Menggunakan Metode Technology Acceptance Model - Rismawan Wisnu Aji; Sinta Novratilova (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
The implementation of the Electronic Medical Record (EMR) system is essential for improving the efficiency of healthcare services. The use of applications in healthcare services, such as the application for providing elective surgery medical record files at the NTB Provincial General Hospital, still faces challenges in its usage. This study aims to evaluate the implementation of elective surgery medical record requests using the Technology Acceptance Model (TAM), which includes aspects of perceived ease of use, perceived usefulness, attitude toward use, behavioral intention, and actual use. This research uses a qualitative method, with data collected through observations and interviews with four informants who regularly use this application. The results show that the perceived ease of use of the application remains low, with many users feeling inexperienced and lacking understanding of how to operate it. On the other hand, perceived usefulness indicates that the application is effective in improving work time efficiency and productivity. Users' attitudes toward the application are considered fairly positive, although there are still obstacles that hinder full acceptance in accordance with the Technology Acceptance Model (TAM). Users’ behavioral intention toward the application is relatively high. The actual use of the application shows that medical record officers use it routinely. Despite technical issues, they remain proactive in seeking solutions for using the system.